Potencial de solubilização de fosfato e identificação molecular de bactérias isoladas de solos sob cultivo de cana-de-açúcar - Castro, Rosa Betânia Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The stillage is a by-product of the production of ethanol and sugar. There is a huge concern for professionals in the environmental area in relation to its final destination, the high degree impactful when discarded into the environment. The plants the sugarcane industry lately have been using the fertilization with vinasse in crops thanks to large concentrations of nutrients present in this effluent. Study on the composition of the microbiota and physiology of soils subjected to irrigation vinasse can be of great importance in finding products of biotechnological interest since this residue enhances the microbial activity in environments where it is applied. The purpose of that study was the molecular characterization, by sequencing the 16S rRNA gene in order to identify the phylogeny of four bacterial isolates obtained from sugarcane cropland with vinasse management, and assess the capacity of phosphate solubilization of these isolated amid NBRIP and relate the data with best practices in agriculture. Isolated LGA01-EV05 showed high sequence similarity to Curtobacterium albidum, isolated LGA02-EV08 denotes similarity to Brevibacillus nitrificans, the LGA03-V20B isolated and LGA04-V20G show high degree of similarity between themselves and with Sinomonas soli. Taxa of isolates are belonging to the phyla Firmicutes and Actinobacteria. As to the evaluation of the bacterial potential for phosphate solubilization, the four isolates were efficient in solubilizing phosphate amid NBRIP. However, it was observed that there was no statistical difference between the LGA02-EV08 and LGA04-V20G groups, with the best phosphate solubilizing bacteria. They had an income about four times the LGA03-V20B group, the worst among the analyzed

A vinhaça é um subproduto resultante da fabricação do etanol e do açúcar. Existe uma enorme preocupação para os profissionais da área ambiental com relação ao seu destino final, pelo elevado grau impactante quando descartada no meio ambiente. As usinas do setor sucroenergético ultimamente vêm utilizando a adubação com vinhaça nas lavouras, graças às grandes concentrações de nutrientes presentes neste efluente. Estudo sobre a composição e a fisiologia da microbiota de solos submetidos à irrigação de vinhaça pode ter grande importância na descoberta de produtos de interesse biotecnológico, uma vez que este resíduo aumenta a atividade microbiana nos ambientes onde é aplicado. O objetivo do referido trabalho foi realizar a caracterização molecular, através do sequenciamento do gene 16S rRNA, a fim de identificar a filogenia de quatro isolados bacterianos obtidos de solos agrícolas de cana-de-açúcar com manejo de vinhaça, assim como avaliar a capacidade de solubilização de fosfato desses isolados em meio NBRIP e relacionar os dados obtidos com boas práticas na agricultura. O isolado LGA01-EV05 mostrou alta similaridade de sequência com Curtobacterium albidum, o isolado LGA02-EV08 denota similaridade com Brevibacillus nitrificans, os isolados LGA03-V20B e LGA04-V20G evidenciam elevado grau de similaridade entre si e com Sinomonas soli. Os táxons dos isolados são pertencentes aos filos Actinobactéria e Firmicutes. Com relação à avaliação do potencial bacteriano para solubilização de fosfato, os quatro isolados demonstraram eficiência em solubilizar fosfato em meio NBRIP. Entretanto, observou-se que não houve diferença estatística entre os grupos LGA02-EV08 e LGA04-V20G, sendo as melhores bactérias solubilizadoras de fosfato. Elas apresentaram um rendimento cerca de quatro vezes superior ao grupo LGA03-V20B, o pior entre os analisados
Keywords: Biotecnologia agricola; Genes; Bactérias; Vinhaça; Solos - Analise; Fosfatos; Biotechnology